The Girl Who Knew Too Much - Quick, Amanda (New York Berkley, 2017)
"Amanda Quick, the bestselling author of Til Death Do Us Part, transports readers to 1930s California, where glamour and seduction spawn a multitude of sins
When rookie reporter Irene Galsson discovers the body of an actress at the bottom of a California hotel pool, she investigates and finds herself drawn to Oliver, a former magician, as the mystery deepens and more women die by drowning.
Keywords: Romantic suspense fiction; Mystery fiction